Quality and Coordination of Care for Persons with Brain Injury in the Community: Developing a Survey - (:unkn) unknown (My University, 2012)
Background: Because of increasing demand on primary care physicians and a complex, fragmented, healthcare "system", people now must coordinate their own healthcare and services. In response, care coordination has become a clinical specialty, typically done by nurses or social workers. People with disabilities (PWD) also must coordinate their care, including health and disability-support services, knowing who to call, advocating for themselves, and scheduling appointments, among other things. Such demands can be particularly problematic after brain injury, which may impair abilities to prioritize, coordinate, manage, and schedule activities. Coordinating services requires participation of the PWD, and supportive significant others (SSO). At present, no validated measures exist which characterize the activities that PWD and SSO do to ensure quality, coordinated care or that identify gaps in needed services. Purpose: Purposes of this thesis were: To continue development of a questionnaire on care coordination; to evaluate its clarity, acceptability, and content validity; and to collect an exploratory description of care coordination experienced be people with TBI and their SSO in the community. Methods: We completed development of the Care and Service Coordination and Management (CASCAM), an exploratory survey with structured quantitative questions and open-ended items, with versions for both the PWD and a SSO. Participants were primarily in the chronic phase of rehabilitation after brain injury. Quantitative results are primarily analyzed using descriptive methods. Interrelationships among items were also examined. Qualitative analyses identified major themes expressed in response to open-ended questions. Results: Content validity was established through verifying that the CASCAM successfully addresses issues related to care and service coordination which apply directly to people with brain injury and their SSO. Participants expressed 7 important themes in the qualitative analysis. The internal consistency of major groups of reported care coordination activities ranged from .774 to .945. Discussions: Care coordination is an essential instrumental activity of daily living for PWD living in the community. The level of internal consistency found strongly suggests that it is possible to provide a summary measure of coordination activities. Further research is needed to develop measures of care coordination to support efforts to improve our fragmented "system" of care.
Keywords: Acquired Brain Injury; Brain Injury; Care Coordination; Occupational Therapy; Service Coordination; Traumatic Brain Injury